Intellectual Property and the Audiovisual Industries - Meir, Christopher; Cucco, Marco; Brembilla, Paola (The Matter of Intellectual Property: Studying the Economic, Political and Cultural Nodes of the Contemporary Media Industries. 15th Media Mutations International Conference, 2025)
This introduction frames intellectual property (IP) as the foundational concept underpinning the audiovisual industries, encompassing legal, economic, cultural, and creative dimensions. The authors argue that IP has been essential to the distribution and monetization of films and television since the inception of cinema, continuing through the massification of television and into the contemporary era marked by video-on-demand platforms and generative artificial intelligence. The issue builds upon recent scholarship examining franchise production, remaking practices, and streaming platforms across Hollywood, European, and global contexts. Current debates are driven by concerns over American streaming platforms' control of IP ownership and uncertainties surrounding AI's use of existing IP and creation of new audiovisual works. These tensions have manifested in high-profile strikes by American guilds and aggressive lobbying efforts for EU directives protecting creative workers, though political responses face challenges due to slow legislative timelines and the low priority afforded to audiovisual policy. The introduction explores contemporary IP management through narrative repurposing practices—including reboots, requels, and legacyquels—that rejuvenate franchises while maintaining affective connections to legacy content. It examines how IPs function as modular, extendible assets managed through multi-layered storytelling mechanisms that differentiate audiences based on familiarity levels, transforming fan knowledge into cultural capital. The collected articles analyze IP from multiple perspectives: legal and authorship challenges posed by generative AI, streaming platform strategies at Paramount+ and Netflix, piracy and fair use, fan editing practices, transnational circulation of Italian television drama, and South Korean industry practices that prioritize IP protection over human wellbeing. Together, these contributions demonstrate IP's position as the central commodity in contemporary media industries, with implications that will only grow in significance.